Światowy kryzys finansowy 2008 w świetle etyki finansów - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2009)
One of the causes of the financial crisis of 2008 can be found in neglecting the norms of business ethics, many of which were broken by bank officers. This claim leads to the global assessment of the new shape of global capitalism, commonly called turbocapitalism. Its financial products are marked by high risk. Hence ethical rules should be recalled as they help to judge actions which bring about many side effects as well as to assess liberal freedom, responsibility and professional integrity. Their application may prevent disastrous decisions made by individuals and financial institutions.